2012
DOI: 10.1007/s12262-012-0682-6
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Study to Compare the Effectiveness of Honey Dressing vs. Povidone Iodine Dressing in Chronic Wound Healing

Abstract: To compare the healing of chronic wounds with honey dressing vs. Povidone iodine dressing in adult subjects with chronic wounds of ≥6 weeks of duration, attending wound care clinic in Surgical Out Patient

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1
5

Year Published

2014
2014
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 15 publications
4
17
1
5
Order By: Relevance
“…edema, hotness, and redness) within 10 days in all patients, which was attributed to the anti-edema and antimicrobial effects of Egyptian honey. Similar findings were observed when several honey samples were tested on more than 787 patients from the nine following countries: Malaysia (Shukrimi et al, 2008), China (Guo & Fu, 2013), Pakistan (Jan et al, 2012), Greece (Kamaratos et al, 2014), Iran (Siavash et al, 2015), Saudi Arabia (Imran et al, 2015), India (Gulati et al, 2014), Yemen (Mohamed et al, 2014) and Russia (Mohamed et al, 2015).…”
Section: Effect Of Honey On Febrile Neutropeniasupporting
confidence: 57%
“…edema, hotness, and redness) within 10 days in all patients, which was attributed to the anti-edema and antimicrobial effects of Egyptian honey. Similar findings were observed when several honey samples were tested on more than 787 patients from the nine following countries: Malaysia (Shukrimi et al, 2008), China (Guo & Fu, 2013), Pakistan (Jan et al, 2012), Greece (Kamaratos et al, 2014), Iran (Siavash et al, 2015), Saudi Arabia (Imran et al, 2015), India (Gulati et al, 2014), Yemen (Mohamed et al, 2014) and Russia (Mohamed et al, 2015).…”
Section: Effect Of Honey On Febrile Neutropeniasupporting
confidence: 57%
“…Research has confirmed that curcumin aids wound healing by stimulating the migration of macrophages, neutrophils and fibroblasts to the wound, accelerates the wound contraction, formation of granulation tissue, neovascularization and reepithelialisation ( Results represented that width of sutured line markedly decreased from day 7 ( Table 1) in all wounds irrespective of treatment. It may supports Gulati et al (2014), where it is indicated that contraction of wound is maximal 5-15 days after injury which is defined as the centripetal movement of wound edges that facilitates closure of a wound defect.…”
Section: Resultsmentioning
confidence: 99%
“…However, in some cases the control group had a better outcome [172], probably promoted by C-I [165], although PVP-I showed worse results than OCT and PHMB in terms of biocompatibility [173]. On the one hand, PVP-I has been shown to be less comfortable than medical honey and less effective in reducing the wound size than silver dressings [174], but on the other hand, it was superior to silver and C-I dressings regarding the amount of pain during medical dressing changes [175]. …”
Section: Iodophorementioning
confidence: 99%